Applying Business Process Re-Engi-neering to Public Sector as A New Public Management Strategy: Understanding the Contra Views and Limits - OBEROI, ROPINDER (Universitas Muhammadiyah Yogyakarta, 2013)
The introduction of Business Process Reengineering (BPR) to the public sector follows the much broader trend of NewPublic Management. BPR in the public sector mostly means amalgamation of business processes, computerization of variousactivities and removal of some unnecessary ones. BPR assimilates a radical premeditated scheme of business pro-cessreengineering and an additional progressive technique of uninterrupted process improvement with adequate informationtechnology (IT) and e-business infrastructure strategies. Public organizations have specific and exclusive features thatdifferentiae-ate them from private sector organizations. Based on the literature review and examining of study find-ings, it isargued that a public sector organization can employ BPR to get better its process and overall organizational performance, if it (1)has accrues a collection of BPR-relevant resources and capabilities; (2) has embarked on BPR with adequate depth and breadth;(3) is developing a post-BPR complementary set of skills, systems and technologies, which are essential to further develop theorganizational impact of the BPR; and (4) has successfully mitigated the effects of BPR implementation problems. In addition toits effect on administration and ser-vice delivery processes through reduction of the processing time, work steps and cost ofgovernment processes, BPR also contributes to enhancing citizen/customer and employee satisfaction, increasing organizationaltransparency and responsiveness which have also become an essential objective of New Public Management. Therefore, publicsectorBPR is emerging as an indispensable to performance of organizations in the developing economy. The essential questionsaddressed in this paper are: What are the scenario and impending problems of reengineering applications in the public sector?Can it be functional for the public sector in attending to frequent problems blockading bureaucracies of developed anddeveloping countries uniformly? What are the implementation vulnerabilities faced by public sector while deploying BPR.